Cationic Amphipathic Antimicrobial Peptides Perturb the Inner Membrane of Germinated Spores Thus Inhibiting Their Outgrowth - Omardien, Soraya; Drijfhout, Jan Wouter; Zaat, Sebastian A.; Brul, Stanley (Frontiers in Microbiology, 2018)
The mode of action of four cationic amphipathic antimicrobial peptides (AMPs) were evaluated against the non-pathogenic, Gram-positive, spore-forming bacterium, Bacillus subtilis. The AMPs were TC19, TC84, BP2 and the lantibiotic Nisin A. TC19 and TC84 were derived from the human thrombocidin-1. Bactericidal peptide 2 (BP2) was derived from the human bactericidal permeability increasing protein (BPI). We employed structured illumination microscopy (SIM), fluorescence microscopy, Alexa 488 labelled TC84, B. subtilis mutants producing proteins fused to the green fluorescent protein (GFP) and single-cell live imaging to determine the effects of the peptides against spores. TC19, TC84, BP2 and Nisin A showed to be bactericidal against germinating spores by perturbing the inner membrane, thus preventing outgrowth to vegetative cells. Single cell live imaging showed that the AMPs do not affect the germination process, but the burst time and generation time. Alexa 488 labelled TC84 suggested that the TC84 might be binding to the dormant spore-coat. Therefore, dormant spores were also pre-coated with the AMPs and cultured on AMP-free culture medium during single-cell live imaging. Pre-coating of the spores with TC19, TC84 and BP2 had no effect on the germination process, but did affect the burst time and generation time. However, the percentage of spores that burst and grew out into vegetative cells was drastically lower when pre-coated with Nisin A, suggesting an application of the peptide against spores. Our findings contribute to the understanding of AMPs and show the potential of AMPs as eventual therapeutic agents against spore-forming bacteria.